Nigam’s pinch test to locate a chronic deep seated small perianal abscess - Nigam, Vinod Kumar; Nigam, Siddharth (International Surgery Journal, 2021)
Background: Nigam’s pinch test (NPT) is for localization of chronic perianal abscess and incision over it. Methods: A description of Nigam’s pinch test and demographics are presented. Results: 20 cases of chronic deep seated perianal abscess were treated with the help of Nigam’s pinch test at Max Hospital, Gurgaon from August 2013 to August 2020. All incisions were directly made over the abscess and in no case a second incision was required. No recurrence and fistula formation occurred. Conclusions: Chronic deep seated perianal abscess usually has no signs except deep pain in perianal area or pain while passing stool. In such cases, there is no visible or palpable swelling, oedema or redness. Sometimes, it becomes difficult to put incision on the right site and more than one incisions are applied. Nigam’s pinch test helps in localization of small deep perianal abscess and correct site of application of incision avoiding multiple incisions. Nigam’s pinch test avoids post operative complications, specially recurrence and fistula-in-ano formation.